Peningkatan Peran dan Performan Inovator untuk Pengembangan Sumber Daya Manusia Pedesaan - Suryana, Asep (Mediator, 2001)
The methodology used in this study was survey. Interview and observation were executed on 100 respondents (innovaators) in Kabupaten Bandung, selected randomly. The unit sampling was 50 respondents on rural area, and 50 respondents on urban area. The result of the study showed that: in the general, there was not significantly different between rural and urban areas in factors of human resources deveopment for innovators’ role and performance; all of respondents needed training and education program in leadership, effective communication, enterpreneurships, management of organization, skill of agriculture, skills of breeding, technology, rural economics, and human resources development; the man or institution hoped by respondents to involve in the program were agriculture instructure, nonformal organizations (non government organization), and university; on cognitive domain: respodents in rural area preferred science and skills of agriculture, breeds, and simple technology, whereas respondents in urban area preferred managerial and startegic aspects, like science of enterpreneurship, human resources development, leadership, and rural economics.